2009
DOI: 10.1186/1472-6874-9-5
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude on maternal health care among rural-to-urban migrant women in Shanghai, China

Abstract: Background: In China, with the urbanization, women migrated from rural to big cities presented much higher maternal mortality rates than local residents. Health knowledge is one of the key factors enabling women to be aware of their rights and health status in order to seek appropriate health services. This study aims to assess the knowledge and attitude on maternal health care and the contributing factors to being knowledgeable among rural-to-urban migrant women in Shanghai.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
69
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 8 publications
10
69
2
Order By: Relevance
“…This study also agreed with the study on the visit of antenatal clinic in Shanghai China, which reported that women attending ANC demonstrated a high degree of knowledge about the importance of visiting ANC and breastfeeding of babies. In addition, they also found that greater numbers of pregnant women were very knowledgeable about child immunization (95.8 percent), 71 per cent of women agreed that antenatal care is necessary, but contrary to the finding of this study, more than half of the women in China did not know the first gestational month that determine their first antenatal visit [18]. In this study, pregnant women expressed satisfaction over the health education package received during ANC visits and acknowledged the Citation: Jibril UN (2017) Awareness and Use of Antenatal Care Services among Women in Edu LGA, Kwara State, Nigeria.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…This study also agreed with the study on the visit of antenatal clinic in Shanghai China, which reported that women attending ANC demonstrated a high degree of knowledge about the importance of visiting ANC and breastfeeding of babies. In addition, they also found that greater numbers of pregnant women were very knowledgeable about child immunization (95.8 percent), 71 per cent of women agreed that antenatal care is necessary, but contrary to the finding of this study, more than half of the women in China did not know the first gestational month that determine their first antenatal visit [18]. In this study, pregnant women expressed satisfaction over the health education package received during ANC visits and acknowledged the Citation: Jibril UN (2017) Awareness and Use of Antenatal Care Services among Women in Edu LGA, Kwara State, Nigeria.…”
Section: Discussioncontrasting
confidence: 97%
“…For example, a study on the use of Ante Natal Care (ANC) showed that 71 percent of women worldwide utilize ANC services and in industrialized countries 95 percent, South Asia -54 percent and SubSaharan Africa 64 percent of women utilize ANC services [11]. Women knowledge is considered one of the key factors that enable them to be aware of their right to health and to seek for appropriate health services [12]. An attitude was viewed as positive or negative evaluation of people, events, activities or ideas in the environment that emerges out of personal experience.…”
Section: Introductionmentioning
confidence: 99%
“…40 The exclusion of migrants from National Health Service Surveys may have biased the results by affecting trends and income inequalities in institutional births in urban areas. Since migrant women usually belong to the lowest income group and seldom use formal services, 41,42 we may have overestimated the proportion of institutional births among the urban poor. Second, rural counties were classified into socioeconomic strata more than 15 years ago and their status could have changed.…”
Section: Discussionmentioning
confidence: 99%
“…According to Zhao et al (2009) education is the most powerful influence on the knowledge score of maternal health. One anecdotal evidence from China study revealed that women who had education of junior high school or higher had a better knowledge level than those who were less educated.…”
Section: Knowledge On Ante-natal Care and Socio-economic Conditionsmentioning
confidence: 99%